Generated alternative options for the possible construction of the organisational structure for the aviation engineering service of aviation units and subunits - Berdochnyk, Dmytro; Dmytriiev, Andrii; Kashaiev , Ihor; Leontiev, Oleksii; Chygryn, Roman (Social Development and Security, 2025)
Purpose: generation of alternative options for building the organisational structure of the aviation engineering service of aviation units and subunits, taking into account the impact of various methods of organising the maintenance of aviation equipment, with their further evaluation and selection of a rational one. Method: analysis and synthesis, methods of military-economic analysis, methods of evaluation. Findings: the research generated alternative options for the organizational structure for the aviation engineering service of aviation units and subunits, taking into account different methods of organizing maintenance. Theoretical implications: the research contributes to the development of scientific approaches to the organization of the aviation engineering service of aviation units, in particular through the use of simulation modelling and multi-criteria evaluation methods to optimize its structure. Practical implications: the results of the research can be used to optimize the organizational structure of the aviation engineering service of aviation units and subunits. Value: the value of the research lies in the development of a scientifically sound approach to optimizing the organizational structure of the aviation engineering service of aviation units and subunits. Future research: further research will be aimed at improving the methodology for optimizing the organizational structure of the aviation engineering service of aviation units using mathematical modelling and military-economic analysis. Papertype: theoretical, practical.